Urban emergence in inuit territory: impacts on the Nunavik socio-ecosystem - Joliet, Fabienne; Chanteloup, Laine; Herrmann, Thora; Gibout, Stéphane; Haillot, Didier; Bhiry, Najat; Coxam, Véronique; Decaulne, Armelle (Comptes Rendus. Géoscience)
Through the combination of interdisciplinary thematics studied on the territory of Nunavik by the OHMi Nunavik, the socio-ecosystem is considered with a focus on the urban context of northern Quebec. Since only a few decades, urbanity (in the geographical sense of the word) is a major change in Nunavik, impacting the traditional indigenous ways of life, geocultural images, food availability and sufficiency, opening new needs regarding energy self-sufficiency, and being impacted by hazards and vulnerability various situations. Therefore, we propose here a reflexive input on the recent urban development and complexity, based on the results of four research projects running since 2015–2017 within the framework of the OHMi Nunavik, Nuna, Niqiliriniq, Siqiniq and Kinngaq.